PENGARUH PENGGUNAAN DOSIS DOLOMIT DAN PEMBERIAN AMELIORAN KCa PADA BERBAGAI JENIS MEDIA TERHADAP PERTUMBUHAN MINI CUTTING - Dwi Nopiyanto; Sulhaswardi Sulhaswardi (UIR Press, 2014)
The objective of this research was to examine the effect of using dolomit and amelioran KCa intereactional and individual on growth of mini cutting for Eucalyptus pellita. The research was conducted at R & D Nursery PT. Arara Abadi during four months from October 2012 to January 2013. The completely randomized design was used by using two factorials. The first factor was P1 (Dolomit 6 kg/m3), P2 (Dolomit 1 g/m3), P3 (Kca 2 kg/m3), and P4 (Kca 5 kg/m3)). The second factor was M1 = Peat Media: CRH (3:1), M2 = Medya CRH: CH (2:1), and M3 = Media CRH: CH (1:2). The observed parameters were plant height, number of leaf, stem diameter, root volume, root lenght, plant biomass, growth percentage, and quality control. The result showed the use of dolomit and ameioran KCa for various media intereactonal had a significant effect on plant height and eukaliptus pelita biomass and the best treatment on the combination between P3M1 and peat media. The using of dolomit and ameioran KCa individually had an effect on plant heiht, number of leaf, stem diameter root volume, and plant biomass with the best treatment on P3 treatment. Treatment of various kinds of medya, individually, effected significantly on plant height, steam diameter, leaf number, root volume, biomass, and quality control with the best treatment of M1(media feat: CRH 3:1).